The Role of Mesh Generation, Adaptation, and Refinement on the Computation of Flows Featuring Strong Shocks - Aldo Bonfiglioli; Renato Paciorri; Andrea Di Mascio (Modelling and Simulation in Engineering)
Within a continuum framework, flows featuring shock waves can be modelled by means of either shock capturing or shock fitting. Shock-capturing codes are algorithmically simple, but are plagued by a number of numerical troubles, particularly evident when shocks are strong and the grids unstructured. On the other hand, shock-fitting algorithms on structured grids allow to accurately compute solutions on coarse meshes, but tend to be algorithmically complex. We show how recent advances in computational mesh generation allow to relieve some of the difficulties encountered by shock capturing and contribute towards making shock fitting on unstructured meshes a versatile technique.